Niels W. Gade: ‘Gegenwartsmusiker’. On Progressive Epigonality in Nineteenth-Century Music History - Oechsle, Siegfried (Danish Yearbook of Musicology, 2019)
Taking stock on Niels W. Gade’s 200th birthday in 2017, various achievements can be pointed out: the catalogue and the critical edition of his works, likewise of his correspondence, a recent biography, numerous recordings etc. However, the Dane is usually reduced to one topos of reception, the ‘Nordic tone’, and categorized into the repository of the ‘Leipzig School’, which, according to respective aesthetic parties, encompasses the time of epigones between Beethoven and Wagner or Beethoven and Brahms. The article takes its starting point from these concepts. The ‘Nordic tone’s north’ is historicoculturally differentiated and distinguished from the context of nationality. Instead of tying it to musical essences of nationality, it is demonstrated that the ‘Nordic tone’ consists of a multitude of characteristic types of orchestral composition. Subsequently, the term ‘Leipzig School’ is examined with regard to categories like canon and epigonality. Primarily, rather than implicit value judgements, their temporal logic is focused on. Led by Schumann’s neologism ‘Gegenwartsmusiker’ (‘musician of the present’), a concept of progress is reconstructed, the subjective autonomy of which might be characterized by the paradox label of ‘progressive epigonality’. Especially for the ‘post-classicist’ years from c. 1830 onwards, it might stimulate an intensified search for structures and perspectives of a European history of music.